Clinico‐Genetic, Imaging and Molecular Delineation of COQ8A‐Ataxia: A Multicenter Study of 59 Patients. Issue 2 (10th June 2020) - Traschütz, Andreas; Schirinzi, Tommaso; Laugwitz, Lucia; Murray, Nathan H.; Bingman, Craig A.; Reich, Selina; Kern, Jan; Heinzmann, Anna; Vasco, Gessica; Bertini, Enrico; Zanni, Ginevra; Durr, Alexandra; et al.
Abstract : Objective: To foster trial‐readiness of coenzyme Q8A (COQ8A)‐ataxia, we map the clinicogenetic, molecular, and neuroimaging spectrum of COQ8A‐ataxia in a large worldwide cohort, and provide first progression data, including treatment response to coenzyme Q10 (CoQ10). Methods: Cross‐modal analysis of a multicenter cohort of 59 COQ8A patients, including genotype–phenotype correlations, 3D‐protein modeling, in vitro mutation analyses, magnetic resonance imaging (MRI) markers, disease progression, and CoQ10 response data. Results: Fifty‐nine patients (39 novel) with 44 pathogenic COQ8A variants (18 novel) were identified. Missense variants demonstrated a pleiotropic range of detrimental effects upon protein modeling and in vitro analysis of purified variants. COQ8A‐ataxia presented as variable multisystemic, early‐onset cerebellar ataxia, with complicating features ranging from epilepsy (32%) and cognitive impairment (49%) to exercise intolerance (25%) and hyperkinetic movement disorders (41%), including dystonia and myoclonus as presenting symptoms. Multisystemic involvement was more prevalent in missense than biallelic loss‐of‐function variants (82–93% vs 53%; p = 0.029). Cerebellar atrophy was universal on MRI (100%), with cerebral atrophy or dentate and pontine T2 hyperintensities observed in 28%. Cross‐sectional (n = 34) and longitudinal (n = 7) assessments consistently indicated mild‐to‐moderate progression of ataxia (SARA: 0.45/year). CoQ10 treatment led to improvement by clinical report in 14 of 30 patients, and by quantitative longitudinal assessments in 8 of 11 patients (SARA: −0.81/year). Explorative sample size calculations indicate that ≥48 patients per arm may suffice to demonstrate efficacy for interventions that reduce progression by 50%. Interpretation: This study provides a deeper understanding of the disease, and paves the way toward large‐scale natural history studies and treatment trials in COQ8A‐ataxia. ANN NEUROL 2020;88:251–263